CHEMICAL COMPOSITION OF THE RABBITS MEAT REARED IN DIFFERENT STOCKING DENSITY - LIMA, KARLA A.O.; CARNEIRO, MARIA I. F.; MOURA, DANIELLA J. (Revista Brasileira de Engenharia de Biossistemas, 2007)
Intensive rabbit’s production is an income-producing economy considering its high breedingcapacity, the easy handling and production in small spaces. However this production isnot free of the problems related to the lack of welfare. The meat presents good nutritionalcharacteristics, and its values have already been established; the alteration in the numberof some of its constituent can be an indicative of such animal was not reared in goodconditions. This research work aimed to evaluate the chemical composition of the meat ofthe New Zealand rabbits reared in different stocking densities. The animals had beendivided in the following treatments: A – 0.09 rabbit m-2, B – 0.072 m-2 and C – 0.06 rabbitm-2 corresponding to 4, 5 and 6 rabbits per cage, respectively. To the 89 days the animalshad been slaughtered for evaluation of the carcass yield. After that the carcasses wereboned, worn out and frozen for determination of the chemical composition (humidity, fat,protein, ashes and phosphorus). The results of the yield and weight of the animals hasbeen: 1163g, 1086g and 1087g, for the treatments, A, B, C respectively. The analysis ofthe chemical composition and its alteration were not affected by the different stockingdensities.